2020
DOI: 10.7554/elife.50722
|View full text |Cite
|
Sign up to set email alerts
|

A polyomavirus peptide binds to the capsid VP1 pore and has potent antiviral activity against BK and JC polyomaviruses

Abstract: In pursuit of therapeutics for human polyomaviruses, we identified a peptide derived from the BK polyomavirus (BKV) minor structural proteins VP2/3 that is a potent inhibitor of BKV infection with no observable cellular toxicity. The thirteen-residue peptide binds to major structural protein VP1 with single-digit nanomolar affinity. Alanine-scanning of the peptide identified three key residues, substitution of each of which results in ~1000 fold loss of binding affinity with a concomitant reduction in antivira… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 86 publications
1
8
0
Order By: Relevance
“…According to the obtained model, TG was able to bind VP1 within the upper part of the five-fold symmetry pore (Figure 4C) formed by the pentameric arrangement of VP1 monomers [23,37]. Notably, these predictions are in line with recent research showing that peptides derived from the two minor capsid proteins VP2 and VP3 of polyomaviruses can bind to the same region of VP1 [38].…”
Section: Tg Interacts With the Gb Glycoprotein Of Hsv-1 And With The ...supporting
confidence: 86%
See 1 more Smart Citation
“…According to the obtained model, TG was able to bind VP1 within the upper part of the five-fold symmetry pore (Figure 4C) formed by the pentameric arrangement of VP1 monomers [23,37]. Notably, these predictions are in line with recent research showing that peptides derived from the two minor capsid proteins VP2 and VP3 of polyomaviruses can bind to the same region of VP1 [38].…”
Section: Tg Interacts With the Gb Glycoprotein Of Hsv-1 And With The ...supporting
confidence: 86%
“…These data suggest that the peptide can bind to the upper region of the 5-fold pore formed by the major capsid component VP1 [23]. Interestingly, recently developed peptides, endowed with effective anti-polyomaviruses properties, were found to bind to the same site on VP1 [38]. In line with this evidence, it has been reported that ligand-induced structural perturbations occurring at the VP1 pore can significantly impair the JCPyV entry process [37], thus explaining the efficacy of TG against this virus.…”
Section: Discussionmentioning
confidence: 89%
“…Remarkably, these pockets correspond to the interaction interface with the minor capsid protein VP2, as observed in the cryo-EM structure of BKV virions 9 and in the X-ray structures of both murine polyomavirus VP1 complexed with truncated VP2 50 and BKPyV VP1 complexed with a thirteen-residue long VP2 derived peptide. 26 Hence the three pockets in the pentamer pore are also likely to be relevant for capsid assembly and function, and should be explored towards rational drug design. A detailed analysis of these pockets and fragments binding therein will be presented elsewhere.…”
Section: Resultsmentioning
confidence: 99%
“…The EC 50 was 0.03 µM for BKPyV and 0.35 µM for JCPyV, and no cytotoxicity was observed in the concentration range tested (Tables 2 and 4). 162 This study demonstrates the principle of direct targeting polyomavirus capsid proteins, but peptide delivery to the relevant sites of replicative disease in the kidney and the brain is unresolved. Also, peptide immunogenicity eliciting neutralizing antibodies and serum sickness after repeated exposure might be problematic.…”
Section: / D1 Min Peptidementioning
confidence: 96%